Reading Center as Community Activity Hubs: An Analysis of Management Effectiveness and Implications for Community Development - Hendrowanto Nibel; Endah Yusma Pratiwi; Syarah Veniaty; Yesninopy Yesninopy (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Aim: This study aims to examine the effectiveness of managing the Ransel Buku community library The research was conducted at Ransel Buku in the lower Petuk Katimpun Village, located along the Rungan River. Method: The researchers employed a qualitative approach with data collection methods including interviews, observations, and document studies. Data analysis utilized the Miles and Huberman technique, which involves data reduction, data display, and conclusion drawing. The validity of the data was ensured through source and technique triangulation. Result and Discussions: The findings indicate that the situational leadership demonstrated by the management is highly adaptive to various conditions. The learning programs include activities such as basic literacy and numeracy (calistung), dancing, English language instruction, as well as counseling and training. The partnership programs reveal collaborations with various institutions. In terms of infrastructure, the facilities and equipment are adequate. Regarding educators, the teaching staff primarily consist of volunteers, while educational roles can still be managed by the management or permanent volunteers. The output indicates the elimination of early marriages among children and their active involvement in activities outside Ransel Buku. The achievement of objectives shows that the primary goal of Ransel Buku to prevent early marriage-has been successfully attained. Additional indicators include community involvement as learners and external support for activities at Ransel Buku, as well as the benefits and satisfaction of service users. Conclusion: In conclusion, the management of Ransel Buku can be considered effective, despite certain shortcomings, such as the absence of professional educators and a formal curriculum.